안와에 발생한 연골종 1예 - 최재환(Jae Hwan Choi), 이동철(Dong Cheol Lee), 김정희(Jeong Hee Kim), 배현식(Hyun sik Bae), 서연림(Yeon Lim Suh), 우경인(Kyung In Woo), 김윤덕(Yoon Duck Kim) (Daihan angwa haghoi jabji, 2018)
목적: 안와에 발생한 연골종(chondroma) 1예를 경험하였기에 이를 보고하고자 한다. 증례요약: 15세 남자 환자가 8개월 전부터 발생한 좌상사시를 주소로 내원하였다. 교정시력은 양안 모두 1.0이었으며, 안구돌출계 검사에서 우안 13 mm, 좌안 13 mm로 좌안의 돌출은 관찰되지 않았으나, 촉진 시 좌안 상비측으로 딱딱한 종괴가 촉지되었다. 안와전산화단층촬영에서 안와 상비측에 비균질한 연부조직음영이 관찰되었으며, 안와 자기공명영상에서 경계가 명확하면서 T1 강조영상에서 저신호강도, T2 강조영상에서 고신호강도를 보이며, 조영증강 T1 강조영상에서 불균질한 조영증강을 보이는 25 × 16 × 20 mm 크기의 종괴가 관찰되었다. 안와종괴 절제생검술을 시행하였으며 조직검사에서 27 × 17 mm 크기의 피막화가 잘된 분엽성 종괴 내에 유리 연골 및 연골세포가 관찰되었으며 연골종으로 진단되었다. 결론: 연골종은 주로 손가락, 발가락 소골 및 장관골에서 주로 발생하며, 드물게 두개골 및 골반골에 발생하는 양성종양이다. 두개골 내에서는 사골동 및 상악골에서 주로 발생하며, 안와에 발생하는 경우는 매우 드물며, 해외에서 몇 증례가 보고되어 있으나 국내에서는 보고된 사례가 없었다. Purpose: To report a case of orbital chondroma. Case summary: A 15-year-old male presented with an 8-month history of left hypertropia. The best-corrected visual acuity was 20/20 in both eyes. The exophthalmometry showed no exophthalmos, with 13 mm in both eyes. There was a hard palpable mass at the superonasal orbit of the left eye. Orbital computed tomography showed a heterogenous soft tissue shadow at the superonasal orbit of the left eye, and orbital magnetic resonance imaging revealed a 25 × 16 × 20 mm well-defined mass with low signal intensity in the T1-weighted image, high signal intensity in the T2-weighted image, and heterogenous enhancement in the contrast enhanced T1-weighted image. The mass was surgically removed with anterior orbitotomy. A 27 × 17 mm well-capsulated lobular mass was found, and histopathological examination revealed hyaline cartilage and chondrocyte. The mass was diagnosed as a chondroma. Conclusions: A chondroma is a benign tumor, which usually occurs in long bones and the small bones of the hands and feet. It is very rare in the facial and pelvic bones. The sites of chondroma occurring in the head and neck include the ethmoid sinus and maxilla, but it is extremely rare in the orbit. KCI Citation Count: 0